Synergistic effect of defocus incorporated multiple segment glasses and repeated low level red light therapy against myopia progression - Yan Yang; Shenghong Liu; Wenwen Gao; Lei Wang; Na Liu; Shiying Zhang; Lianjing Yang; Lingyun Cheng (Scientific Reports)
Abstract Defocus incorporated multiple segment (DIMS) lenses and repeated low-level red-light (RLRL) are used to retard myopia progression. However, it is currently unknown if there is a synergistic effect of the two interventions. In the current study, 190 school-aged children with myopia (380 eyes) were studied for the change in axial length (AL) over nearly one year of follow-up. Of 380 eyes, 170 eyes wore DIMS lenses, 80 eyes had RLRL therapy, and 130 eyes had both interventions (DIMS_RLRL) for myopia control. AL changes were calculated at each follow-up visit by subtracting the baseline measurements and normalized to yearly changes in mm. AL changes as a primary outcome were analyzed in a generalized linear mixed model to compare effect sizes of myopia control among three interventions while adjusting for age, sex, baseline axial length, and follow-up length. Participants had a mean age of 9.84 ± 2.63 years old, mean AL of 24.49 ± 1.20 mm, mean SER of -2.90 ± 2.08 diopters, and mean follow-up time of 301 ± 91 days. By the end of the study, the adjusted mean yearly axial change with combination therapy was − 0.13 mm, -0.04 mm for the eyes with RLRL alone, and 0.16 mm for the eyes with DIMS lenses alone (p < 0.0001). Combination therapy of DIMS and RLRL has significantly greater effect size in controlling myopia progression than either RLRL alone (p = 0.0009) or DIMS alone (p < 0.0001).